The academic impact of online mathematics learning during COVID-19 for junior high school students - I Putu Wisna Ariawan (Jurnal Elemen, 2022)
Until now, no research explicitly examines the academic impact on public junior high school students in Singaraja City. The actual condition of the academic impact of online mathematics learning is necessary to be revealed immediately. This information can be used as a basis for teachers designing and implementing mathematics learning to minimize or eliminate the negative impact of online learning. This study involved 507 public junior high school students distributed over four public schools in Singaraja City as the sample. This study used a questionnaire instrument consisting of 14 items, and the data were tabulated based on the responses entered on the google form. The study results showed that students experienced several academic impacts as a result of online learning of mathematics. The academic impacts that students most felt among others: the amount of mathematics material was hard to understand, students doubted the accountability of the grade obtained by their friends, decreased enthusiasm for learning, and students felt that their academic abilities were e not optimal. The conclusion obtained from this study is that online mathematics learning  during COVID-19 had an academic impact on public junior high school students in Singaraja City.